Determination of NPF on the Sustainability of BPRS Microfinance : non-Performing Financing (NPF) in BPRS - Najib, Mohamad Ainun; Suhartini, Nani (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2026)
This study examines how non performing financing (NPF) in BPRS in Banten and West Java is impacted by operational efficiency (BOPO), liquidity (FDR), Islamic financial inclusion, and governance (GCG). Panel data regression analysis is used in this study's quantitative technique to evaluate the influence of independent factors on the dependent variable. A total of 175 panel observations were utilized in the analysis, which was based on the findings of panel data regression analysis on 35 BPRS from 2019 to 2023. The observations were made during a five-year period using yearly or quarterly panel data. NPF is significantly impacted positively by BOPO and FDR, but negatively by GCG and finance. The four factors together accounted for 28.03 percent of the variance in NPF. In order to track the sustainability of Islamic microfinance, this emphasizes the significance of efficiency, risk assessment, financial knowledge, and governance. This study aims to offer insights that could enhance the stability and governance of BPRS, particularly in regions characterized by significant institutional density and challenges related to financial inclusion. This study combines four main variables simultaneously in measuring NPF as an indicator of microfinance sustainability, offering a more comprehensive approach compared to previous partial studies